Analisis Sistem Pengendalian Intern Pengeluran Kas pada CV. Manik Arsa - Arif Rahman Hakim; I Gusti Ayu Purnamawati (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to determine the implementation of the internal control system for cash disbursements and to find out the results of the evaluation of the internal control system for cash disbursements at CV. Arsa bead. This research is classified as a qualitative research research. This type of research is used to obtain information on the phenomena that occur in CV. Arsa bead. Based on the results of this study, it is found that if the elements of the control environment in CV. Manik Arsa is sufficient, the element of risk assessment in CV. Arsa beads are inadequate. This is due to the evidence of cash disbursements, which can be changed at the expense of the road money that has been inputted. If the information system does not have control, the numbers or names in the application can be changed easily or the related invoices can be destroyed, then cash theft can easily occur.